Global asymptotic stability of neutral type fractional‐order memristor‐based neural networks with leakage term, discrete and distributed delays. (24th February 2021) - Syed Ali, M.; Hymavathi, M.; Saroha, Sumit; Krishna Moorthy, R.
Abstract : This paper is concerned with the global asymptotic stability of the neutral type fractional‐order memristor‐based neural networks with leakage discrete and distributed delays. By building a sensible Lyapunov fractional related with integral and fractional derivative terms, a few satisfactory conditions comprehensively asymptotic stability is gotten. At that point, the global asymptotically stability investigation of fractional‐order neural systems utilizes the results from the obtained LMI conditions. Finally, numerical examples are provided to illustrate the effectiveness of the established of the proposed results.